Historical Consciousness of Hamka's Interpretation of Al-Baqarah Verse 261 and Its Relevance to the History of Educational Institutions in Indonesia - Tarman, Al-Faiz Muhammad Rabbany; Safii, Ridwan Maulana; Yanuri, Yusuf Rohmat (Borneo : Journal of Islamic Studies, 2025)
Interpreter cannot help but be confined to a limited space and time in an effort to interpret the Qur'an. The interpreter is influenced by the externalization of his environment and the internalization of various knowledge. This research discusses the awareness of Hamka's historical influence in the interpretation of QS. al-Baqarah verse 261 and its relevance to the history of educational institutions in Indonesia. This research focuses on three things, namely the treasures of the interpretation of QS. al-Baqarah verse 261, Hamka's concept of education, and the history of national educational institutions that show Hamka's historical influence in the interpretation of the verse. This research uses the theory of “effective-historical consciousness” from Hans-George Gadamer. The conclusion of this research is, first, spending wealth in the way of Allah is not limited to jihad and hajj, but also all virtuous deeds. Second, Hamka has great attention to the field of education. Hamka's concept of education contains four important keywords, namely the function of reason, the integration of science and religion, the purpose of education, and gender equality. Third, before the existence of formal education in the form of schools, mosque, langgar and surau education were known. Then in the corridor of colonization of the archipelago, the Portuguese and Dutch colonizers established schools in the context of spreading religion and colonization. Meanwhile, during the Japanese colonization, the quantity of schools decreased. This limited number and quality faced by Hamka is one indication of the influence of history in Hamka's interpretation in Al-Azhar.